Sanksi Pidana bagi Pelaku Penyebaran Berita Hoaks serta Ujaran Kebencian dengan Memakai Akun Anonym - I wayan Denny Syaputra; I Made Arjaya; Diah Gayatri Sudibya (Warmadewa Press, 2020)
Crime in cyberspace is a crime with computer technology, especially the internet. One example is the spread of hoaxes and expressions of hatred. This research was conducted to determine the arrangements for spreading hate speech based on positive law, the legal consequences arising when someone is proven to spread hate speech and spread hoaxes, and efforts and steps taken to prevent the spread of hoax news and hate speech so as not to spread in the community. This research is a type of normative legal research with a statutory approach and conceptual approach. Arrangements for the dissemination of hoax news and expressions of hatred based on positive law have been explicitly regulated in the Criminal Code, which is found in Article 154 of the Criminal Code, Article 154a, Article 156, Article 156a, and Article 157 paragraph (1) and paragraph (2). Besides being regulated in the Criminal Code utterances of hate are regulated outside of the Criminal Code, including in Law No.40 of 2008 concerning the Elimination of Racial and Ethnic Discrimination, which is contained in Article 16, and is also regulated in Law No. 19 of 2016 concerning Renewal of Law No. 11 of 2008 concerning ITE has also regulated the distribution of hate speech through cyberspace, which is contained in article 27, article 28 paragraph (1) and paragraph (2), article 40 paragraph (2) and article 45 paragraph (2) due to the law incurred if someone is proven to have committed a crime of spreading hoax hoaxes and expressions of hatred can be jailed for 2 years, 3 years and even up to 10 years